Uncorrected Nucleotide Bias in mtDNA Can Mimic the Effects of Positive Darwinian Selection - Albu, Mihai (Oxford University Press, 2008)
The relative rates of nucleotide substitution at synonymous and nonsynonymous sites within protein-coding regions have been widely used to infer the action of natural selection from comparative sequence data. It is known, however, that mutational and repair biases can affect rates of evolution at both synonymous and nonsynonymous sites. More importantly, it is also known that synonymous sites are particularly prone to the effects of nucleotide bias. This means that nucleotide biases may affect the calculated ratio of substitution rates at synonymous and nonsynonymous sites. Using a large data set of animal mitochondrial sequences, we demonstrate that this is, in fact, the case. Highly biased nucleotide sequences are characterized by significantly elevated dN/dS ratios, but only when the nucleotide frequencies are not taken into account. When the analysis is repeated taking the nucleotide frequencies at each codon position into account, such elevated ratios disappear. These results suggest that the recently reported differences in dN/dS ratios between vertebrate and invertebrate mitochondrial sequences could be explained by variations in mitochondrial nucleotide frequencies rather than the effects of positive Darwinian selection.